Evaluasi Status Kesuburan Tanah Entisol pada Beberapa Umur Tanaman Kelapa Sawit (Elaeis guineensis Jacq) di Desa Sungai Ambangah Kabupaten Kubu Raya - Batubara, Yuli Shinta Natalia; Manurung, Rinto; Hazriani, Rini (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2026)
Entisols have considerable potential for plantation development, including oil palm (Elaeis guineensis Jacq), a strategic commodity in Indonesia’s economy. In Sungai Ambangah Village, oil palm cultivation constitutes a primary livelihood activity. This study aimed to assess soil fertility status under different ages of oil palm plantations established on Entisols. The research was conducted in Sungai Ambangah Village, Sungai Raya Subdistrict, Kubu Raya Regency, West Kalimantan, Indonesia. Soil sampling was performed using a zig-zag pattern within the palm circle area. Each observation point consisted of five subsamples composited into a single sample, resulting in a total of twelve composite samples collected from three land units. Soil samples were analyzed at the Laboratory of Soil Chemical Properties and Fertility, Faculty of Agriculture, Universitas Tanjungpura. Analytical results were classified according to the soil chemical property criteria established by the Soil Research Center (1983), and soil fertility status was evaluated based on the guidelines of the Soil Research Center, Bogor (1995). The results indicated that organic C, available P, and total K contents were relatively high. However, overall soil fertility remained constrained due to very acidic soil pH, very low base saturation, and limited availability of exchangeable base cations (Ca, Mg, K, and Na). Fertility evaluation revealed that the soils were classified as low fertility status, with very low base saturation identified as the primary limiting factor associated with strongly acidic soil conditions.